Implementasi Model Pembelajaran Daring pada masa Pandemi Covid-19 di Kelas IV SDN Tondokerto Tahun Ajaran 2020/2021 - Laras Widia Ningrum; Moh Aniq Khairul Basyar; Singgih Adhi Prasetyo (STKIP Andi Matappa Pangkep, 2022)
This research is based on the government's policy to enforce online learning in schools. The purpose of this study is to determine the implementation of online learning at SD Negeri Tondokert. This research method is a descriptive qualitative research. The data sources of this research are teachers, fourth grade students. The data obtained from this research are in the form of interviews and documentation. Based on the research findings from the analysis and discussion that have been described, the researchers obtained the results of the analysis that the implementation of online learning in class IV SDN Todokerto utilized various applications including whatsapp, google foam, zoom meeting,. For the evaluation given by the teacher to students through test paper and google form. The weakness in online learning is that the material cannot be conveyed in its entirety, and there are still many students who do not have their own devices, on the other hand online learning has advantages including being flexible, it can be done anytime and anywhere, teachers and students can use applications such as Google Forms, Zoom Meetings. In online learning, of course, there are supporting factors, including gadgets, internet networks, as well as parents and the environment.